Feedback regulation of heat shock factor 1 (Hsf1) activity by Hsp70-mediated trimer unzipping and dissociation from DNA - Kmiecik, Szymon; Le Breton, Laura; Mayer, Matthias P. (The EMBO journal, 2020)
Abstract The heat shock response is a universal transcriptional response to proteotoxic stress orchestrated by heat shock transcription factor Hsf1 in all eukaryotic cells. Despite over 40 years of intense research, the mechanism of Hsf1 activity regulation remains poorly understood at the molecular level. In metazoa, Hsf1 trimerizes upon heat shock through a leucine-zipper domain and binds to DNA. How Hsf1 is dislodged from DNA and monomerized remained enigmatic. Here, using purified proteins, we demonstrate that unmodified trimeric Hsf1 is dissociated from DNA in vitro by Hsc70 and DnaJB1. Hsc70 binds to multiple sites in Hsf1 with different affinities. Hsf1 trimers are monomerized by successive cycles of entropic pulling, unzipping the triple leucine-zipper. Starting this unzipping at several protomers of the Hsf1 trimer results in faster monomerization. This process directly monitors the concentration of Hsc70 and DnaJB1. During heat shock adaptation, Hsc70 first binds to a high-affinity site in the transactivation domain, leading to partial attenuation of the response, and subsequently, at higher concentrations, Hsc70 removes Hsf1 from DNA to restore the resting state.
Gesehen am 21.09.2020